(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
The article examines contemporary, evidence-based approaches to the effective training of youth in track and field athletics, emphasizing the alignment of training methodologies with biological maturation stages, long-term athlete development principles, and individualized programming. Key components include phased developmental models from foundational movement literacy in pre-pubertal years to event-specific specialization post-puberty integrated periodization strategies, synergistic strength and plyometric training, event-tailored technical drills, injury prevention protocols, nutritional optimization, psychological support mechanisms, and technology-assisted monitoring. The synthesis demonstrates that maturation-aligned, diversified training yields superior performance outcomes, reduced injury risk, enhanced psychological resilience, and sustainable athletic careers compared to early specialization paradigms. These methods collectively promote not only elite-level achievement but also lifelong physical literacy and well-being among young athletes.